Impact of uniform and non-uniform heated rods on free convective flow inside a porous enclosure: finite element analysis. (14th May 2021) - Yasin, Amna; Ullah, Naeem; Saleem, S; Nadeem, Sohail; Al-Zubaidi, A
Abstract: A numerical study of laminar natural convective flow in a porous rectangular cavity having two heated rods is performed in this article. Both heated rods are placed in the middle of the cavity. Further, it is assumed that the flow and isothermal contours are influenced by permeable medium. Physical laws transform this physical setup into the mathematical form, which is expressed as partial differential equation. Finite element method is adopted to get the solution of these partial differential equations, the results against various flow controlling variables are presented in contour plots and line graphs. Results illustrate that in the case of non-uniform heating, the heat transfer rate is suppressed with the enhancement Rayleigh parameter as compared to uniform heating. In addition, with the increase in heated length of rods, flow field gets stronger due to stronger buoyancy effects. Moreover, the velocity distribution and Nusselt number are enhanced with the rise of permeability of porous medium.